Relationship Between Sleep Quality and Incidence of Acne Vulgaris in Students of the Faculty of Medicine, Baiturrahmah University Batch of 2020 - Irma Primawati; Leonny A Ningsih; Mashdarul Ma’arif (Institute of Computer Science (IOCS), 2022)
Acne Vulgaris (AV) is a chronic skin condition caused by blockage or inflammation of the hair follicles and sebaceous glands known as pilosebaceous units. The cause of AV is not known with certainty but AV is a multifactorial disease because many factors influence the onset of acne vulgaris, namely sebum, hormones, stress, genetics, diet, and cosmetics. Poor sleep quality is also a factor influencing the onset of AV and is thought to lead to increased androgen hormone activity. Androgen hormones can trigger polysebaceous glands to produce excessive sebum on the face which then results in the emergence of AV, so that AV occurs more easily on skin that tends to be oily than dry or normal skin. The purpose of this study was to determine the relationship between sleep quality and the incidence of acne vulgaris in students of the Faculty of Medicine, Baiturrahmah University Batch 2020. The type of research used was an analytical observational study with a case control study design. The population in this study were students of the Faculty of Medicine, Baiturrahmah University Batch 2020. The sampling technique of this study used a purposive sampling technique. The samples obtained were 88 people who had done the inclusion and exclusion criteria. The results showed that the gender of the most respondents was female, namely 64 respondents (72.7%), the sleep quality of the most respondents was poor, namely 67 respondents (76.1%), the incidence of acne vulgaris based on gender was mostly female (36.4%). , and the relationship between sleep quality and the incidence of acne vulgaris was more common in students with poor sleep quality (38.6%). The conclusion of this study, there is no relationship between sleep quality and the incidence of acne vulgaris in students of the Faculty of Medicine, Baiturrahmah University batch 2020.